Verifying the Existence of Indigenous Peoples using a Socio-spatial Approach: A Case Study of the Boti Tribe, Indonesia - Dako, Fransiskus Xaverius; Setyowati, Retno; Herningtyas, Wieke; Pujiono, Eko; Budiman , Iman; Oematan, Oskar Krisantus (Institut Pertanian Bogor (IPB University), 2024)
Minister of Home Affairs Regulation Number 52 of 2014 states that the criteria or evidence that must be met for recognition of indigenous peoples are: indigenous history, customary territories, customary law, customary objects, and customary institutions. Using a case study of the Boti Tribe, the oldest ethnic group on Timor Island, this study aims to collect evidence of the existence of indigenous peoples and their customary territories. This research will focus on verifying evidence of the existence of indigenous peoples using a socio-spatial approach. Our findings show that the Boti indigenous community still exists, with several main evidences of its existence, namely, they have a traditional history in which they were formed from several clans led by the Benu clan; there is a customary area with several use zones of land; there are customary laws that regulate daily life and local wisdom in managing natural resources; and there are traditional practices. Additional evidence was discovered that they manage customary forests sustainably, as evidenced by the consistent forest cover over the last 30 years. These findings can be used to develop academic papers and plans for regional regulations concerning the Boti Tribe's recognition.